PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Asep Sulahudin; Rambat Nur Sasongko (Manajer Pendididikan, 2019)
Abstract: The purpose of this study is to describe the management of islamic religious education in public Junior High school 2 Muara Pinang. This research method using qualitative method, data collected by interview, observation, and decumentation. The subject of this study were head of shool, vice curricula, Islamic religious education teacher, and students. The results of this study are the teachers of islamic religious education at the beginning tool, the implementation of islamic religious education teacher learning using varied methods and classroom management, learning evaluation using the concept of cognitive, affegtive, and psikomotori, Islamic religious education teacher problem and conduct MGMP religious education of islam. Keyword: Learning management, Islamic Religious Education.